The Oxford handbook of phenomenologies and organization studies - Vaujany, François-Xavier de, 1974-; Aroles, Jeremy, 1989-; Perézts, Mar (Oxford handbooks, 2023)
This handbook shows the unexpected richness and diversity of key phenomenological and post-phenomenological thinkers in an aim to help management and organization scholars to understand a huge variety of contemporary phenomena such as AI, digitalization of organizational processes, remote work, financial markets, and much more.